Video in teacher learning : through their own eyes - Baecher, Laura Hope (Thousand Oaks : Corwin, 2020)
Harness the power of video to promote reflective practice and teacher growth Video is the only feedback method that allows educators to view their teaching through their own eyes, yet many K-12 professionals have yet to reap the benefits of this powerful technology. This practical and comprehensive guide takes advantage of new methods and tools to capture teaching and learning and a broad base of current research to impact teacher thinking and actions. Written for instructional coaches, administrators, supervisors, and individual teachers, it includes guidance on how to get started and how to engage in nonjudgmental and descriptive analysis scaffolding to counter anxiety and resistance, and to cultivate a growth mindset. chapters on specific contexts including developmental, evaluative, and problems of practice. guidance for observation in specific grade bands and for specific student populations. templates and links to videos for video analysis tasks, step-by-step process outlines, real-world vignettes and application questions. Drawing on broad evidence of the impact of video on teaching, this is the guide for maximizing this powerful form of professional learning.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Reflective teaching; Career development